Modelação do processo de decisão de compra de bens alimentares - Matos, Paula Carvalho (2011)
Classifications of the JEL Classification System: 1st: M - Business Administration and Business Economics; Marketing; Accounting; M3 - Marketing and Advertising; M31 - Marketing 2nd: F - International Economics; F1 – Trade; F18 - Trade and Environment